Steady transformation of primeval forest into subalpine pasture during the Late Neolithic to Early Bronze Age (2300-1700 BC) in the Silvretta Alps, Switzerland - Dietre, Benjamin; Reitmaier, Thomas; Walser, Christoph; Warnk, Theresa; Unkel, Ingmar; Hajdas, Irena; Lambers, Karsten; Reidl, Daniel; Haas, Jean Nicolas (The Holocene, 2020)
The question of the origin of Alpine farming and pastoral activities associated with seasonal vertical transhumance and dairy production in the Silvretta Alps (Eastern Switzerland) has recently benefitted from renewed interest. There, pastoral practises began during the Late Neolithic (2300 BC), but alpine dairy farming was directly evidenced so far only since the Late Bronze Age/Early Iron Age (1300-500 BC). The vegetation development, timberline shifts at 2280 m a.s.l. and environmental conditions of the subalpine Urschai Valley (Canton of Grisons, Switzerland) were reconstructed for the small (8 m2) Plan da Mattun fen based on palynological and geochemical analyses for the last six millennia. The X-ray fluorescence (XRF) analyses are among the first ones performed on a European peatland in such altitudes. A high Rb/Sr ratio in the fen peat sediments revealed an increase in catchment erosion during the time when the forests of the Upper Urschai Valley were steadily diminished probably by fire and livestock impact (2300-1700 BC). These landscape openings were paralleled by increasing micro-charcoal influx values, suggesting that prehistoric people actively set fire on purpose. Simultaneously, palynological evidence for pastoralism was revealed, such as pollen from typical herbs indicating livestock trampling, and abundant spores from coprophilous fungi. Since then, vertical transhumance and pastoral activities remained responsible for the open subalpine landscape above 2000 m a.s.l., most probably also in the context of milk and dairy production since 1300 BC, which is characteristic for the European Alps until today.